Surgical treatment of aberrant nail fold hypertrophy secondary to chronic onychocryptosis - Gabriela T. Batiston; Julia C. K. El Dib; Juliana V. Alvarenga; Lucas S. Madureira; João R. Antonio (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Onychocryptosis, popularly known as "ingrown toenail", is defined as an inflammatory condition of the lateral nail fold resulting from the ingrowth of the lateral edge of the nail plate into the lateral nail fold, which occurs most frequently in the hallux. It is a reason for great demand for primary health care and is sometimes associated with disabling pain and, therefore, a frequent reason for absenteeism from work. Nail fold hypertrophy is a common consequence of onychocryptosis. Therefore, the present study reports an exuberant case of lateral nail fold hypertrophy treated surgically in a patient with chronic onychocryptosis.